Technetium-99m stannous phytate versus technetium-99m sulfur colloid for sentinel lymph node mapping in breast cancer - Chunhuai Liao; Jian Lu; Luz Angela Torres-de la Roche; Rudy Leon De Wilde; Tao Liu; Wenjie Shi; Qiang Wang; Yicheng Jiang; Rui Zhuo; Maya Sophie de Wilde (Medicine, 2026)
This study compares technetium-99m stannous phytate (99mTc-PHY) plus methylene blue versus technetium-99m sulfur colloid (99mTc-SC) plus methylene blue for sentinel lymph node (SLN) imaging in early-stage breast cancer (BC). We retrospectively reviewed early-stage BC patients treated from 2019 to 2024. All underwent sentinel lymph node biopsy using either 99mTc-PHY with methylene blue or 99mTc-SC with methylene blue as tracers. A Neoprobe 2000r detector was used to locate nodes. A total of 1151 patients were enrolled in the study, of whom 669 received 99mTc-SC and 482 received 99mTc-PHY (mean age 52 years). The SLN detection rates were 98.8% and 97.3%, respectively ( P = .06). The positive SLN rates for metastasis (14.8% vs 11.7%; P = .13) and the median SLN counts were comparable (4 vs 3; P = .27). In multivariable analysis, higher tumor stage (T1–T2) but not histological type (ductal or lobular) was independently associated with increased SLN count in both groups (T1: incidence rate ratios = 1.318; T2: incidence rate ratios = 1.686; both P < .001). The rate of axillary lymph node dissection was found to be significantly lower in the 99mTc-SC group (26.5% vs 43.6%; P = .03). However, the reasons for this difference were not identified. No perioperative adverse events were reported. The present findings provide support for the use of 99mTc-PHY as a feasible tracer in the context of SLN detection in BC patients, thus exhibiting no statistically significant difference in detection rates compared to 99mTc-SC.